A abordagem experimental nas séries iniciais do ensino de Ciências: desafio para os professores do ensino fundamental - Fernandes, Juliana Ferreira (2021)
This study analyzes the conceptions of Science teachers from the Initial Grades of Elementary School, from a municipal school in the state of Mato Grosso do Sul, regarding the importance and applicability of experimentation in Science Teaching. The general objective of the investigation is to analyze the impediments and difficulties pointed out by teachers for the little use of the Experimental Scientific Approach in Science classes in the early years. With a quantitative-qualitative nature, the investigation uses bibliographical research and empirical data collection through a semi-structured questionnaire with the school teachers, who made their considerations about the experimentation in their formation and the teaching practice in the classroom. The Iramuteq software is used to process the data collected from the teachers. The reflection on experimentation will be systematized through considerations of dialogic education proposed by Paulo Freire and theorists who discuss experimentation in Science Teaching, such as Angotti (2015), Giacomini (2015), Pernambuco (2002) and Delizoicov (2008). The results show that the applicability of experimentation is still considered a great challenge by teachers, being little developed in pedagogical practice. Teachers point out the lack of specific materials to carry out the experimentation, such as glassware and a laboratory, and the priority of activities aimed at literacy, as some obstacles present in teaching practice, contributing to the non-inclusion of experimental classes in their teaching practices. It is hoped that this work can contribute to teachers in discussing the topic, motivating their interest and curiosity, demystifying beliefs and provoking reflection on the need to mediate knowledge in experimentation.